Evaluation of drought tolerance of Malaysian rice genotypes through morphological study, grain yield and drought tolerance indices - Nulit, Rosimah; Seok, Christina Yien Yong; Chee, Kong Yap; Ibrahim, Mohd Hafiz; Sidek, Noorhazira; Evamoni, Fatematuz Zuhura; Mohiuddin, A. K. M. (Agri Bio Research Publishers, 2024)
Drought tolerant rice genotypes are required to lessen yield losses and boost overall production. The study aimed at examining drought tolerance level of 15 rice genotypes during reproductive stage released by MARDI. Drought was applied at early reproductive stage and continued until harvesting, while for control continuous water supply was maintained since the beginning. Drought significantly reduced the morphological growth and development. All genotypes showed a significant difference in the mean grain yield under drought stress when compared with control, indicating that the performance under water stress was considerably different. The mean grain yield ranged from 686.46 to 906.25 g/m2 under wellwatered condition, whereas 0.00 to 96.88 g/m2 under stressed condition. MR211 represented maximum yield in both the conditions, while MR219 and MR220 had no yield under drought stress. The hierarchical clustering grouped all the genotypes into different clusters based on their similarity. MR307, MR303 and MR284 were similar in performances for most of the studied traits thus grouped in same cluster could be considered as drought-tolerant. Three genotypes (MR211, MR253 and MR263) revealed good performances for grain yield and morphological traits were grouped together in cluster II. MARDI WANGI88, MR219, MR220, MR269, MARDI WARNA98, MR157, MR167, MR185 and MR297 were incorporated in cluster I and could be concluded as drought susceptible genotypes. In conclusion, the study implied that the variances among genotypes for the studied traits were sufficient to assess drought tolerance in rice.